2023
DOI: 10.1002/mp.16862
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low dose CT scanning for PET/CT

Samaneh Mostafapour,
Marcel Greuter,
Johannes H. van Snick
et al.

Abstract: BackgroundThe use of computed tomography (CT) for attenuation correction (AC) in whole‐body PET/CT can result in a significant contribution to radiation exposure. This can become a limiting factor for reducing considerably the overall radiation exposure of the patient when using the new long axial field of view (LAFOV) PET scanners. However, recent CT technology have introduced features such as the tin (Sn) filter, which can substantially reduce the CT radiation dose.PurposeThe purpose of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This is markedly lower compared with the study of Işıkçı et al [4] that observed radiation exposure from CT scans on the foetus ranging between 8.5 and 16.0 mGy. Moreover, advancements such as the use of tin filters during LDCT acquisition could dramatically reduce radiation exposure for AC by as much as 90%, as recently demonstrated by Mostafapour et al [10]. Applying the tin filter to our LDCT scans will reduce the foetal radiation exposure by eight to ten times, resulting in a foetal radiation exposure ranging between 0.09 and 0.11 mGy when the foetus is included in the FOV.…”
Section: Discussionmentioning
confidence: 75%
“…This is markedly lower compared with the study of Işıkçı et al [4] that observed radiation exposure from CT scans on the foetus ranging between 8.5 and 16.0 mGy. Moreover, advancements such as the use of tin filters during LDCT acquisition could dramatically reduce radiation exposure for AC by as much as 90%, as recently demonstrated by Mostafapour et al [10]. Applying the tin filter to our LDCT scans will reduce the foetal radiation exposure by eight to ten times, resulting in a foetal radiation exposure ranging between 0.09 and 0.11 mGy when the foetus is included in the FOV.…”
Section: Discussionmentioning
confidence: 75%